2015
DOI: 10.1097/mbc.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis in young adult with familial protein S deficiency

Abstract: Hereditary thrombophilia is the inherited predisposition to venous or, occasionally, arterial thrombosis. In most cases, it is because of changes related to physiological coagulation inhibitors or mutations in genes of coagulation factors. Protein S, a vitamin K-dependent plasma glycoprotein, is a natural anticoagulant and its deficiency is associated with familial venous thrombosis. We present a case study that brings together two rare diseases, cerebral venous thrombosis (CVT) and familial protein S deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…CVST is rarely seen in association with PSD. Amaral et al 9 reported a case of CVST in a young adult with familial PSD but the patient and his family members did not receive PROS1 genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…CVST is rarely seen in association with PSD. Amaral et al 9 reported a case of CVST in a young adult with familial PSD but the patient and his family members did not receive PROS1 genetic testing.…”
Section: Discussionmentioning
confidence: 99%